2009
DOI: 10.3767/003158509x461486
|View full text |Cite
|
Sign up to set email alerts
|

<I>Geoglossomycetes</I> cl. nov., <I>Geoglossales</I> ord. nov. and taxa above class rank in the <I>Ascomycota</I> Tree of Life

Abstract: Featuring a high level of taxon sampling across Ascomycota, we evaluate a multi-gene phylogeny and propose a novel order and class in Ascomycota. We describe two new taxa, Geoglossomycetes and Geoglossales, to host three earth tongue genera: Geoglossum, Trichoglossum and Sarcoleotia as a lineage of ‘Leotiomyceta’. Correspondingly, we confirm that these genera are not closely related to the genera Neolecta, Mitrula, Cudonia, Microglossum, Thuemenidum, Spathularia and Bryoglossum, all of which have been previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 58 publications
6
48
1
Order By: Relevance
“…Our results for the MCM7 gene are in agreement with Schoch et al's study as Geoglossomycetes is shown as a monophyletic group with strong MLBS and BPP support (Fig 2, Table 4), but, however, without strong support for its placement in relation to other classes of Leotiomyceta as noted previously (Schoch et al 2009b). We did not recover support for the expanded subclass Pleosporomycetidae as found in a previous multi-gene study focused only on Dothideomycetes (Schoch et al 2009c) and the influence of additional gene data and improved taxon sampling cannot be ruled out.…”
Section: Class-level Relationshipssupporting
confidence: 82%
See 2 more Smart Citations
“…Our results for the MCM7 gene are in agreement with Schoch et al's study as Geoglossomycetes is shown as a monophyletic group with strong MLBS and BPP support (Fig 2, Table 4), but, however, without strong support for its placement in relation to other classes of Leotiomyceta as noted previously (Schoch et al 2009b). We did not recover support for the expanded subclass Pleosporomycetidae as found in a previous multi-gene study focused only on Dothideomycetes (Schoch et al 2009c) and the influence of additional gene data and improved taxon sampling cannot be ruled out.…”
Section: Class-level Relationshipssupporting
confidence: 82%
“…We show that all classes in the present study are monophyletic, which corroborates earlier hypotheses by Eriksson and Winka (1997). Recently, Schoch et al (2009b) proposed a new class, Geoglossomycetes, based on a multi-gene phylogeny.…”
Section: Class-level Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many character evolution studies have been carried out within the past 15 years (e.g. Liu and Hall 2004;Li et al 2005;Schoch et al 2009;Schmitt 2011;Kumar et al 2012). However still there are many incomplete points to resolve.…”
Section: Character Evolution Studiesmentioning
confidence: 99%
“…The discussion on p. 419 fails to catch up with the creation of class Geoglossomycetes and order Geoglossales by Schoch et al (2009), except that their view is vaguely hinted at in the preface. The last paragraph on p. 419 points out that Thuemenidium atropurpureum belongs to Leotiomycetes (Ohenoja et al, 2010, Schoch et al, 2009), but it is here retained in Geoglossaceae. Microglossum, another genus best placed in Leotiomycetes, is also retained.…”
Section: Species Descriptionsmentioning
confidence: 84%